UK trainee experience in interstitial lung disease: results from a British Thoracic Society survey. Issue 2 (28th October 2014) - Sharp, Charles; Maher, Toby M; Welham, Sally; Gibbons, Michael
Abstract : Interstitial lung disease (ILD) is a growing field of respiratory medicine in which novel therapies are emerging. It is important that trainees gain competence and confidence in this area. To explore the training experiences of specialty trainees, we conducted a survey of their practical experience and confidence in diagnosing and managing ILD.